Phylogeny and diversification history of the large Neotropical genus Philodendron (Araceae): Accelerated speciation in a lineage dominated by epiphytes. Issue 6 (11th July 2018) - Canal, Dubán; Köster, Nils; Jones, Katy E.; Korotkova, Nadja; Croat, Thomas B.; Borsch, Thomas
Abstract : Premise of the Study: Philodendron is a large genus of ~560 species and among the most conspicuous epiphytic components of Neotropical forests, yet its phylogenetic relationships, timing of divergence, and diversification history have remained unclear. We present a comprehensive phylogenetic study for Philodendron and investigate its diversification, including divergence‐time estimates and diversification rate shift analyses. Methods: We performed the largest phylogenetic reconstruction for Philodendron to date, including 125 taxa with a combined dataset of three plastid regions ( petD, rpl16, and trnK/matK ). We estimated divergence times using Bayesian evolutionary analysis sampling trees and inferred shifts in diversification rates using Bayesian analysis of macroevolutionary mixtures. Key Results: We found that Philodendron, its three subgenera, and the closely related genus Adelonema are monophyletic. Within Philodendron subgenus Philodendron, 12 statistically well‐supported clades are recognized. The genus Philodendron originated ~25 mya and a diversification rate upshift was detected at the origin of subgenus Philodendron ~12 mya. Conclusions: Philodendron is a species‐rich Neotropical lineage that diverged from Adelonema during the late Oligocene. Within Philodendron, the three subgenera currently accepted are recovered in two lineages: one contains the subgenera Meconostigma and Pteromischum and the other contains subgenus Philodendron . The lineage containing subgenera Meconostigma and Pteromischum underwent a consistent diversification rate. By contrast, a diversification rate upshift occurred within subgenus Philodendron ~12 mya. This diversification rate upshift is associated with the species radiation of the most speciose subgenus within Philodendron . The sections accepted within subgenus Philodendron are not congruent with the clades recovered. Instead, the clades are geographically defined.